Why John Mandeville’s "Travel book" was written? - Olga Togoeva (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The article is devoted to the “Travel Book” which was written by John Mandeville in the middle of the 14th century and remained extremely popular over the next few centuries. The author of the article describes the handwritten and the first-printed traditions of the existence of the “Book”, dwells on the circumstances of its origin, on the problem of its authorship and on the content of its two parts. Based on the analysis of numerous miracles, both quite real and fictional, which John Mandeville mentions while describing his adventures in the Middle East, Africa, Asia and distant exotic countries, the author of the article comes to the conclusion that the “Travel Book” was not a typical medieval travelogue, but it rather belonged to the genre of didactic literature. John Mandeville tried to teach his contemporaries a lesson about what it means to be a true Christian, how a person can approach the Lord and His plan for creating everything on earth, what ideas and values ру should share at the same time. In particular, Mandeville constantly returns to the idea of a new Crusade, which remained extremely popular in the middle of the 14th century, but he criticizes it on the grounds that Europeans should not plan to conquer foreign lands (even the Holy Land) without solving their own internal, primarily moral, problems.